Simulating optical coherence tomography for observing nerve activity: A finite difference time domain bi-dimensional model. - Francesca Troiani; Konstantin Nikolic; Timothy G Constandinou (PLoS ONE)
We present a finite difference time domain (FDTD) model for computation of A line scans in time domain optical coherence tomography (OCT). The OCT output signal is created using two different simulations for the reference and sample arms, with a successive computation of the interference signal with external software. In this paper we present the model applied to two different samples: a glass rod filled with water-sucrose solution at different concentrations and a peripheral nerve. This work aims to understand to what extent time domain OCT can be used for non-invasive, direct optical monitoring of peripheral nerve activity.